Proposed upgrading work for Terminal Sultan Azlan Shah Airport at Jalan Lapangan Terbang, Ipoh, Perak Darul Ridzuan for Airport Malaysia Berhad / Deddy Iskandar Mazlan - Mazlan, Deddy Iskandar (Faculty of Architecture, Planning and Surveying, 2005)
The purpose of this final project is to realise the design process that involve in the preliminary findings, analysis case study and synthesizing. The suggested title of this project is Proposed Uprading Terminal Sultan Azlan Shah Airport Ipoh. Before writing this documentation, a lot of procedures has to be met and must follow a systematic process. Various important factors must be considered especially inside the angular space including environment outside the building. The first step is to identify constraints and limitations of the existing site, interior and exterior spaces. This is important as to identify the problem solving of the project. The research begins from basic design principles up to the building roof. Besides that, the research of interior space must also be considered as a case study. The nature of the case study directly or indirectly related to the project that I have proposed. In fact, a planning proposal was made before I started to do a new design. Several important aspects must be considered to ensure the space function, such as to fulfill user’s needs and comfort. The design made should fulfill the character of users or visitors demand and also match the concepts that need to be shown. By proposed uprading, it is hoped that it will be able to give benefits to the tourist, our people and country.